Les Répercussions d’Un Réseau Ethnique Et La Dynamique Entrepreneuriale Des Libanais En Côte d’Ivoire - Zanga, Ouattara Mohamed; Jérôme, Aloko-N’guessan (European Scientific Journal, ESJ, 2018)
Our objective in this article is to understand the characteristics of the entrepreneurship of the population of Lebanese origin in Côte d’Ivoire from the perspective of the ethnic network. In other words, it is about appreciating impacts of the Lebanese ethnic network on the development of their entrepreneurial activities, by scrutinizing the modalities such as the support for the immigration, the departure in business, the discovery of the entrepreneurial opportunity, the financing of the entrepreneurship and even the motive in the entrepreneurial commitment. To this end, this article joined within the framework of the studies relative to the ethnic and/or immigrant entrepreneurship. This research thus left the Anglo-Saxon literature on the ethnic entrepreneurship and a field survey to seize how the ethnic network constitutes a major element of the economic integration of the Lebanese by the entrepreneurship in Côte d’Ivoire. In fact, their ethnic network of the Lebanese boosts their entrepreneurship through a shape of selection in the immigration; the family unit - by the tourism or the visit of the family - organizing the arrival of the new migrant until the obtaining of its first employment pending the acquisition of the Ivorian experience or the capital of the future business and the discovery of the entrepreneurial opportunity.